Cross-Coupling Reactions with Methyl Esters as Electrophiles - Daneshfar, Omid (Université d'Ottawa / University of Ottawa, 2022)
Constructing C-C and C-heteroatom bonds is of the utmost importance in organic chemistry. Cross-coupling is a reaction where a transition metal catalyst facilitates the formation of a C-C or C-heteroatom bond between two coupling partners. Cross-coupling reactions are often very robust and reliable and thus have established themselves as one of the most powerful and versatile tools for the modern synthetic organic chemist. A great area of modern cross-coupling research has been the expansion of electrophiles that can participate in cross-coupling reactions. By expanding the scope of available electrophiles, one can access a greater variety of products from simpler starting materials. Esters are relatively robust scaffolds and are difficult to engage in cross-coupling reactions due to the substantial double-bond character of the C(acyl)-O bond. Developing methods to functionalize esters via cross-coupling reactions would be highly beneficial as esters are ubiquitous and readily available. The cross-coupling of phenyl esters has been relatively well established throughout the past decade. The cross-coupling of simple methyl esters largely remains elusive in the primary literature. Chapter 1 of this thesis provides a detailed literature background on the field of carboxylic acid derivative cross-coupling, with a primary focus on esters. Chapter 2 describes our efforts in discovering new methodologies for methyl ester cross-coupling reactions. We invoked the use of high throughput experimentation (HTE) studies to facilitate our search for novel methyl ester cross-coupling reactivity. Chapter 3 describes our efforts in developing an additive free, Ni-catalyzed transesterification reaction of methyl esters. The use of alcohols as nucleophilic coupling partners for methyl esters has yet to be reported. We obtained a scope of 20 isolated examples and were able to identify scaffolds that could not be tolerated under our reaction conditions. Lastly, we began preliminary reaction kinetics studies in order to gain useful mechanistic insights for methyl ester cross-coupling reactions.
Keywords: Esters; Ni-Catalysis; Cross-coupling; Acyl electrophile; C(acyl)-O bond